Epistemic value - Haddock, Adrian; Millar, Alan, Ph. D.; Pritchard, Duncan (Oxford : Oxford University Press, 2009)
Recent epistemology has reflected a growing interest in issues about the value of knowledge and the values informing epistemic appraisal. Is knowledge more valuable that merely true belief or even justified true belief? Is truth the central value informing epistemic appraisal or do other values enter the picture?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of